The longitudinal association between natural outdoor environments and mortality in 9218 older men from Perth, Western Australia. (April 2019) - Zijlema, Wilma L.; Stasinska, Ania; Blake, David; Dirgawati, Mila; Flicker, Leon; Yeap, Bu B.; Golledge, Jonathan; Hankey, Graeme J.; Nieuwenhuijsen, Mark; Heyworth, Jane
Abstract: Background/Aim: Natural outdoor environments may mitigate harmful environmental factors associated with city living. We studied the longitudinal relationship between natural ('green and blue') outdoor environments and mortality in a cohort of older men residing in Perth, Western Australia. Methods: We studied a cohort of 9218 men aged 65 years and older from the Health In Men Study. Participants were recruited in 1996–99 and followed until 2014, during which 5889 deaths were observed. Time-varying residential surrounding greenness based on the Normalized Difference Vegetation Index, and the number and size of parks, natural space and waterbodies were defined to characterize the natural outdoor environment. All-cause non-accidental and cause-specific mortality was ascertained with the Western Australian Data Linkage System. The association of the natural outdoor environment with mortality was examined using Cox regression analysis. Results: After adjusting for age, men living in the highest quartile of cumulative average surrounding greenness had a 9% lower rate of all-cause non-accidental mortality (95% confidence interval [CI] 0.84, 0.98; p  = .013) compared with those in the lowest quartile. This association was no longer present after adjustment for other risk factors, especially level of education. Living within 500 m of one (vs. no) natural space was associated with decreased mortality risk (adjusted hazard ratio 0.93; 95% CI 0.86, 1.00; p  = .046), but no association with mortality was found for two or more natural spaces compared to none and for parks. Associations between waterbodies and mortality were inconsistent, showing non-linear beneficial and harmful associations. Conclusions: In this longitudinal study of older men residing in Perth, we observed evidence suggestive of an association between access to natural spaces and decreased mortality. Associations between surrounding greenness and mortality seemed to be confounded by level of education, and associations with waterbodies were complex and need to be studied further. Highlights: 9218 men aged 65+ years from Perth, Western Australia were studied from 1996 to 2014. Residential surrounding greenness, parks, natural space and waterbodies were mapped. Associations between surrounding greenness and mortality were confounded by education. Living close to one (vs. no) natural space was associated with decreased mortality risk. Associations between waterbodies and mortality were inconsistent.